Geneza i skutki nowelizacji art. 55 Konstytucji RP. Spojrzenie z punktu widzenia ustrojodawcy - Karski, Karol (Kwartalnik Prawa Publicznego, 2012)
The accession of Poland to the European Union in 2004 necessitated implementation into the Polish legal order of a number of EU legal instruments, including the Council Framework Decision of 13 June 2002 on the European arrest warrant (EAW) and the surrender procedures between Member States (2002/584/JHA). However, its provisions contravened Article 55(1) of the Constitution of the Republic of Poland, under which extradition of a Polish citizen was prohibited. In its judgment of 27 April 2005, the Polish Constitutional Tribunal concluded that statutory provisions implementing the Framework Decision would loose force after 18 months. It also recommended – since it was not able to impose an obligation on the Constitution Makers – that the Constitution be amended. In the judgment the Tribunal ruled that surrender was “merely a kind (type, special form) of extradition”. The judgment referred directly to the EAW. However, its conclusions also indirectly questioned the constitutionality of the ratification by Poland, in 2001, of the Rome Statute of the International Criminal Court (ICC). Already at that time a large number of Polish legal scholars did not agree that surrender was not a form of extradition. The Polish Constitution-Makers started working on this problem in 2006 and concluded that extradition of Polish citizens – regardless of its form – could not be unconditional. They upheld the general constitutional rule that it should be prohibited, but they introduced some exceptions. These refer to all forms of extradition, including “classic” extradition and the EAW. Thus, the Constitution-Makers ruled that extradition of a Polish citizen could be granted upon a request made by a foreign state or an international judicial body, if such a possibility stemmed from an international treaty ratified by Poland or from a statute implementing a legal instrument of an international organisation of which Poland was a member. In such a case extradition of a Polish citizen is possible, only provided that the act covered by a request for extradition was committed outside the territory of Poland and constituted an offence under the law in force in Poland, or, if the act had been committed within the territory of Poland, provided that it constituted an offence under the law in force in Poland both at the time of its commitment and at the time of the making of the extradition request. The condition that the act be committed outside Poland and the condition of dual criminality do not apply, if an extradition request is made by an international judicial body established under an international treaty ratified by Poland in connection with a crime of genocide, crime against humanity, war crime or a crime of aggression, covered by the jurisdiction of that body. In this way the Constitution-Makers found as appropriate not to introduce the above restrictions with regard to extradition granted on the request of the ICC. Therefore, the amendment validated the ratification of the ICC Statute, ratification which was made in 2001 in contravention of the Constitution. At the same time the Polish Constitution-Makers affirmed the existing constitutional rule – referring not only to Polish citizens but also to foreigners – whereby extradition was forbidden, if it concerned a person suspected of committing a crime for political reasons but without the use of force. They also added a constitutional provision – inspired by the case-law of Germany’s Federal Constitutional Court – whereby extradition violating human and civil rights and freedoms was inadmissible. These rules are applicable to all forms of extradition. It must be stressed that the catalogue of conditions of extradition enumerated in the Constitution is by no means complete. It can be expanded by treaty or statutory provisions. However, it cannot in any way be reduced. The Constitution-Makers also reaffirmed the constitutional rule according to which the admissibility of extradition was decided by courts. It means that if a Polish court has not granted its consent, no extradition from Poland is possible. This example shows that in a sovereign state the Constitution-Makers cannot be forced to do anything. There can only be attempts to persuade them. To what extent such attempts can be successful is a separate question. As an emanation of the Nation, the Constitution-Makers independently define models to which all other acts within the national legal system must conform. The rule should be that the Constitution must be amended before the state wants to take on external obligations that do not fully conform to it. They must not be taken on assuming that, if the situation demands it, the Constitution will either be interpreted in a manner that is “favourable” to the acts violating it or it will “simply” be amended. The Constitution can never be “simply” amended. The amendment in question remedied the consequences of the ratification of the ICC Statute, which contravened the Constitution, and – insofar as it was acceptable to the Constitution-Makers – brought the execution of the EAW by Polish institutions against Polish citizens closer to the standards described in the Council Framework Decision 2002/584/JHA. When working on the amendment, the Constitution-Makers noted, inter alia, that there had been suggestions in the European, especially German, legal doctrine that there was a necessity for the substance of the Framework Decision to be changed. A renegotiation of such a legal instrument is, after all, one of the methods of adapting the national legislation to the substance of external norms.